Teaching and Researching: Identifying Problems and Finding Solutions Through Classroom Action Research (CAR) - Indahri, Yulia; Djahimo, Santri E.P. (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2018)
This paper presents several key issues about what teachers should do in their (EFL) classes, in relation to their main job as teachers (i.e. teaching) and additional job for their professional development (i.e. researching). The main aim of this paper is to provide insightful information for teachers and teacher candidates about how they can improve themselves through teaching and researching activities, In addition, it also aims to discuss a particular way for them to be able to identify problems as well as find solutions in their own classroom through Classroom Action Research (CAR). Makalah ini menyajikan beberapa isu utama tentang apa yang harus dilakukan guru dalam kelas (EFL) mereka, dalam kaitannya dengan pekerjaan utama mereka sebagai guru (yaitu mengajar) dan pekerjaan tambahan untuk pengembangan profesional mereka (yaitu penelitian). Tujuan utama dari makalah ini adalah untuk memberikan informasi yang mendalam bagi para guru dan calon guru tentang bagaimana mereka dapat meningkatkan diri mereka sendiri melalui kegiatan mengajar dan meneliti, Selain itu, juga bertujuan untuk membahas cara tertentu bagi mereka untuk dapat mengidentifikasi masalah serta temukan solusi di ruang kelas mereka sendiri melalui Penelitian Tindakan Kelas (CAR).